Nonlinear spin waves in magnetic thin films - foldover, dispersive shock waves, and spin pumping - Janantha, Pasdunkorale Arachchige Praveen, author; Wu, Mingzhong, advisor; Eykholt, Richard, committee member; Marconi, Mario, committee member; Patton, Carl, committee member (Colorado State University. Libraries, 2016)
Three nonlinear phenomena of spin waves and the spin Seebeck effect in yttrium iron garnet (YIG)/Pt bi-layer structures are studied in this thesis and are reported in detail in Chapters 4-7. In the fourth chapter, the first observation of foldover effect of nonlinear eigenmodes in feedback ring systems is reported. The experiments made use of a system that consisted of a YIG thin film strip, which supported the propagation of forward volume spin waves, and a microwave amplifier, which amplified the signal from the output of the YIG strip and then fed it back to the input of the strip. The signal amplitude vs. frequency response in this ring system showed resonant peaks which resulted from ring eigenmodes. With an increase in the resonance amplitude, those resonant peaks evolved from symmetric peaks to asymmetric ones and then folded over to higher frequencies. The experimental observations were reproduced by theoretical calculations that took into account the nonlinearity-produced frequency shift of the traveling spin waves. The fifth chapter presents the first experimental observation of the formation of envelope dispersive shock wave (DSW) excitations from repulsive nonlinear spin waves. The experiments used a microwave step pulse to excite a spin-wave step pulse in a YIG thin film strip, in which the spin-wave amplitude increases rapidly. Under certain conditions, the spin-wave pulse evolved into a DSW excitation that consisted of a train of dark soliton-like dips with both the dip width and depth increasing from the front to the back and was terminated by a black soliton that had an almost zero intensity and a nearly 180 degree phase jump at its center. The sixth chapter reports on the spin pumping due to traveling spin waves. The experiment used a micron-thick YIG strip capped by a nanometer-thick Pt layer. The YIG film was biased by an in-plane magnetic field. The spin waves pumped spin currents into the Pt layer, and the later produced electrical voltages across the length of the Pt strip through the inverse spin Hall effect (ISHE). Several distinct pumping regimes were observed and were interpreted in the frame work of the nonlinear three-wave splitting processes of the spin waves. The seventh chapter presents the first experimental work on the roles of damping in the spin Seebeck effect (SSE). The experiments used YIG/Pt bi-layered structures where the YIG films exhibited very similar structural and static magnetic properties but very different damping. The data indicate that a decrease in the damping of the YIG film gives rise to an increase in the SSE coefficient, and this response shows quasi-linear behavior. The data also indicate that the SSE coefficient shows no notable dependences on the enhanced damping due to spin pumping.